Endophthalmitis in Silicone Oil-Filled Eyes - Magdalene Yin Lin Ting; Soyang Ella Kim; Rodrigo Anguita (MDPI AG, 2023)
Incidences of post pars plana vitrectomy (PPV) endophthalmitis vary between 0.02% and 0.13%, and infectious endophthalmitis in silicone oil-filled eyes is even rarer. We performed a literature review to describe the incidence, protective and predisposing factors, causative pathogens, management options, and prognosis of infectious endophthalmitis in silicone oil-filled eyes. Various studies have elucidated different aspects of this condition. Causative pathogens commonly include commensals. Traditional management involves the removal of silicone oil (SO), intravitreal antibiotics and then SO re-injection. Alternatively, injecting intravitreal antibiotics into silicone oil-filled eyes has also been reported. Visual prognoses are uniformly guarded. Due to the uncommon nature of this condition, studies are limited either by their retrospective design or by small sample sizes. However, observational studies, case series, and case reports can play an important role in rare conditions until larger studies are conducted. This comprehensive review aims to summarise the information available in the literature, to act as a good source for ophthalmologists looking for answers on this topic, and to suggest areas for future development.